Non-Esterified Fatty Acid-Induced Apoptosis in Bovine Granulosa Cells via ROS-Activated PI3K/AKT/FoxO1 Pathway - Zhiqi Lei; Ilyas Ali; Min Yang; Caixia Yang; Yifei Li; Lian Li (MDPI AG, 2023)
Non-esterified fatty acid (NEFA), one of negative energy balance (NEB)'s most well-known products, has a significant impact on cows' reproductive potential. Our study used an in vitro model to investigate the deleterious effects of NEFA on bovine granulosa cells (BGCs) and its underlying molecular mechanism. The results showed that high levels of NEFA led to the accumulation of reactive oxygen species (ROS), increased the expression of apoptosis-related factors such as Bcl2-Associated X/B-cell lymphoma-2 (Bax/Bcl-2) and Caspase-3, and down-regulated steroid synthesis-related genes such as sterol regulatory element binding protein 1 (SREBP-1), cytochrome P450c17 (CYP17), and cytochrome P450 aromatase (CYP19), to promote oxidative stress, cell apoptosis, and steroid hormone synthesis disorders in BGCs. In addition, NEFA significantly inhibited phosphatidylinositol 3-kinase (PI3K) and phosphorylated protein kinase B (p-AKT) activity and increased forkhead box O1 (FoxO1) expression. To further explore the role of the PI3K/AKT/FoxO1 signaling pathway in NEFA, we found that pretreatment with AKT-specific activator SC79 (5 mg/mL) for 2 h or transfection with FoxO1 knockdown siRNA in BGCs could alleviate the negative effects of NEFA treatment by decreasing Bax/Bcl-2 ratio and Caspase-3 expression, and upregulating SREBP-1, CYP17, and CYP19 expression. Meanwhile, SC79 significantly inhibited NEFA-induced dephosphorylation and massive nuclear translocation of FoxO1. Taken together, the NEFA induced oxidative stress, apoptosis, and steroid hormone synthesis disorders in BGCs by inhibiting the PI3K/AKT pathway that regulates FoxO1 phosphorylation and nuclear translocation. Our findings help to clarify the molecular mechanisms underlying the negative effects of high levels of NEFA on BGCs.